Agrobacterium rhizogenes: paving the road to research and breeding for woody plants - Ying, Wei; Wen, Guangchao; Xu, Wenyuan; Liu, Haixia; Ding, Wona; Zheng, Luqing; He, Yi; Yuan, Huwei; Yan, Daoliang; Cui, Fuqiang; Huang, Jianqin; Zheng, Bingsong; et al. (Frontiers in Plant Science, 2023)
Woody plants play a vital role in global ecosystems and serve as valuable resources for various industries and human needs. While many woody plant genomes have been fully sequenced, gene function research and biotechnological breeding advances have lagged behind. As a result, only a limited number of genes have been elucidated, making it difficult to use newer tools such as CRISPR-Cas9 for biotechnological breeding purposes. The use of Agrobacterium rhizogenes as a transformative tool in plant biotechnology has received considerable attention in recent years, particularly in the research field on woody plants. Over the past three decades, numerous woody plants have been effectively transformed using A. rhizogenes-mediated techniques. Some of these transformed plants have successfully regenerated. Recent research on A. rhizogenes-mediated transformation of woody plants has demonstrated its potential for various applications, including gene function analysis, gene expression profiling, gene interaction studies, and gene regulation analysis. The introduction of the Ri plasmid has resulted in the emergence of several Ri phenotypes, such as compact plant types, which can be exploited for Ri breeding purposes. This review paper presents recent advances in A. rhizogenes-mediated basic research and Ri breeding in woody plants.2 This is a provisional file, not the final typeset article This study highlights various aspects of A. rhizogenes-mediated transformation, its multiple applications in gene function analysis, and the potential of Ri lines as valuable breeding materials.